Experience, evidence, and sense the hidden cultural legacy of English - Wierzbicka, Anna. (New York ; Oxford : Oxford University Press, 2010)
In this volume, Anna Wierzbicka demonstrates that three uniquely English words - evidence, experience, and sense - are linchpins. Using a rigorous plain language approach to meaning analysis she unpackages the dense cultural meanings of these key words disentangles their multiple meanings, and traces their origins.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English language -- Semantics; English language -- Social aspects; Language and languages -- Philosophy